wyznacz iloczyn: a) x(pot.2)+x-1)(x(pot.2)-x+1)
b) 4x(pot2)(2x(pot5)-2x(pot2))



Odpowiedź :

Lea3

a)

[tex]( {x}^{2} + x - 1)( {x}^{2} - x + 1) = {x}^{4} - {x}^{3} + {x}^{2} + {x}^{3} - {x}^{2} + x - {x}^{2} + x - 1 = {x}^{4} - {x}^{2} + 2x - 1 [/tex]

b)

[tex]4 {x}^{2} (2 {x}^{5} - 2 {x}^{2} ) = 8 {x}^{7} - 8 {x}^{4} [/tex]

MertB

Cześć!

Szczegółowe wyjaśnienie:

a)     (x² + x -1) (x² - x + 1) = x⁴ - x³ + x² + x³ - x² + x - x² + x - 1 = x⁴ - x² + 2x - 1

b)     4x² (2x⁵ - 2x²) = 8x⁷ - 8x⁴

Pozdrawiam,

MrBarte!